The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/acer.14590
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic changes due to early, chronic intermittent alcohol exposure during forebrain development implicate WNT signaling, cell‐type specification, and cortical regionalization as primary determinants of fetal alcohol syndrome

Abstract: Background Fetal alcohol syndrome (FAS) due to gestational alcohol exposure represents one of the most common causes of nonheritable lifelong disability worldwide. In vitro and in vivo models have successfully recapitulated multiple facets of the disorder, including morphological and behavioral deficits, but far less is understood regarding the molecular and genetic mechanisms underlying FAS. Methods In this study, we utilized an in vitro human pluripotent stem cell‐based (hPSC) model of corticogenesis to prob… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 101 publications
(149 reference statements)
2
15
0
Order By: Relevance
“…Neural progenitor cells in general have been shown to be less affected by ethanol-induced cell death (Santillano et al, 2005). Furthermore, previous studies have shown that compared to very high doses of EtOH, more moderate doses, such as that used in this study, do not result in significant cell death (Fischer et al, 2021). As already mentioned, apoptosis may not be accurately detected using scand snRNAseq.…”
Section: Discussionmentioning
confidence: 65%
“…Neural progenitor cells in general have been shown to be less affected by ethanol-induced cell death (Santillano et al, 2005). Furthermore, previous studies have shown that compared to very high doses of EtOH, more moderate doses, such as that used in this study, do not result in significant cell death (Fischer et al, 2021). As already mentioned, apoptosis may not be accurately detected using scand snRNAseq.…”
Section: Discussionmentioning
confidence: 65%
“…At 7 days, cells in each group were collected and used for IF ( n = 6), WB ( n = 6), and RT-PCR ( n = 6). The medium with the same alcohol concentration was changed regularly everyday to maintain the alcohol concentration (Ethanol evaporation after 24 h was 10–20%) (Fischer et al, 2021 ). To analyze the concentration-dependent effect of alcohol, cells were exposed to varying concentrations of alcohol (0, 30,100 mM) (Tomas et al, 2005 ).…”
Section: Methodsmentioning
confidence: 99%
“…Symptom severity of FAS varies greatly with timing, duration, and dose of alcohol exposure and genetic and metabolic factors (Burd et al, 2003 ). In vitro and in vivo models have successfully summarized multiple aspects of the disorder, including morphological and behavioral defects—still, the molecular and genetic mechanisms underlying FAS are poorly understood (Fischer et al, 2021 ). Astrocytes are the most abundant glial cells in the brain (Han et al, 2020 ), whose main functions include providing nutrients to the neuron, maintaining the extracellular ion balance, releasing transmitters, regulating synaptic plasticity, maintaining synaptic connection, and so on (Acosta et al, 2017 ; Palmer and Ousman, 2018 ; Munger et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Foetal alcohol syndrome (FAS) is one of the most severe types of FASD [ 2 ]. Many aspects of FASD disorder have been successfully summarised in vitro and in vivo, including morphological and behavioural defects, but the pathogenesis of the disease is still unclear [ 3 , 4 ]. The unawareness of pregnancy or addictive alcoholism in women during pregnancy has led to FASD in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Almost all current research on the pathogenesis of FASD has focused on neurons [ 4 ]. Alcohol can trigger a robust neurodegenerative response and neuronal apoptosis [ 14 , 15 ] and impact synaptic formation [ 1 , 16 ].…”
Section: Introductionmentioning
confidence: 99%